Random binary sequences generation using heartbeats for cryptographic keys in WBSNs. (24th March 2022) - Sinha, Aditya Kumar; Mahapatro, Judhistir; Bhabani, Bidisha
Random binary sequences (RBSs) from heartbeats as a cryptographic key is an emerging biometric-based authentication technique in wireless body sensor networks (WBSNs). Patients' health is monitored in real-time using sensor devices and telemedicine is provided remotely. These devices are small, and resource constrained, so, implementing computationally heavy cryptographic algorithms inside these devices for secure transmission of data is a challenging task. In this paper, a novel approach is proposed to produce a 128 bit RBS using heartbeats. This can be used as a cryptographic key to aid in secure communication. To generate an RBS, cyclic block encoding and convolutional encoding is applied on a single heartbeat to obtain 32 bit encoded value. Four consecutive heartbeats' 32 bit encoded value is concatenated to obtain 128 bit RBS. This 128 bit RBS is subjected to various tests to verify the cryptographic key strength and is analysed for optimal resource consumption.